1993
DOI: 10.1152/ajpendo.1993.264.4.e599
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of muscle and liver to glucose-fatty acid cycle in humans

Abstract: To examine the influence of elevated free fatty acid (FFA) levels on hepatic glucose production (HGP) and oxidative and nonoxidative pathways of glucose metabolism, 12 healthy subjects participated in two euglycemic insulin-clamp studies performed with and without infusion of Intralipid plus heparin. To elucidate the role of skeletal muscle in this putative interaction, we performed muscle biopsies for the measurement of activities of glycogen synthase (GS), pyruvate dehydrogenase (PDH), and carnitine palmitoy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
67
2
1

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 29 publications
5
67
2
1
Order By: Relevance
“…It is suggested that prolonged hyperlipidemia may contribute to the increased production of glucose via increased expression of this protein. Taken together with numerous other reports on the impact of lipids on carbohydrate metabolism in skeletal muscle (7)(8)(9), liver (8)(9)(10)12,13), and pancreatic (3-cells (11,38,39), our finding provides experimental support for the role of hyperlipidemia in the pathogenesis of NIDDM (40,41).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It is suggested that prolonged hyperlipidemia may contribute to the increased production of glucose via increased expression of this protein. Taken together with numerous other reports on the impact of lipids on carbohydrate metabolism in skeletal muscle (7)(8)(9), liver (8)(9)(10)12,13), and pancreatic (3-cells (11,38,39), our finding provides experimental support for the role of hyperlipidemia in the pathogenesis of NIDDM (40,41).…”
Section: Discussionsupporting
confidence: 87%
“…It also suggests that the mechanism(s) by which a sustained increase in the availability of lipids might affect hepatic glucose output involves more than the short-term increase in the rate of gluconeogenesis (15). Indeed, increased hepatic glucose production is an early (~1 week) consequence of high-fat feeding in rodents (34), and the plasma FFA levels are closely related to the rate of endogenous glucose production in humans (8)(9)(10)12,13). Furthermore, most patients with NIDDM display increased concentrations of plasma FFA throughout the day (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, abnormalities in hepatic insulin receptor level and function have been sought in a variety of animal models of Type 2 diabetes (NIDDM) [10][11][12]. On the other hand, it has also been shown that hepatic insulin resis-tance can be produced by acute elevation of nonesterified fatty acids (NEFA) [13][14][15]. Excess lipid levels have been shown to stimulate gluconeogenesis, but the enzymatic mechanism responsible is not fully understood [16].…”
mentioning
confidence: 99%
“…Among them, high free fatty acid (FFA) levels could partially account for insulin resistance in NIDDM patients [8]. It has recently been reported that healthy subjects increased plasma FFA levels induced by lipid-heparin administration impair insulin-mediated increase in peripheral glucose uptake [9][10][11][12][13] and suppression of HGP under euglycemic hyperinsulinemic conditions [13,14]. In patients with NIDDM, circulating plasma FFA concentrations are increased in postabsorptive and postprandial states [15].…”
mentioning
confidence: 99%